Perancangan Rekonfigurasi Link Transmisi Microwave Long Haul IV Nagari – Kamang Baru dengan Space Diversity Menggunakan Pathloss 5.0 - Wiwi Alfiyani (LPPM Institut Teknologi Telkom Purwokerto, 2019)
Cellular communication is a very important requirement so need to improve the performance of the telecommunications system, especially in area with obstacles such as IV Nagari - Kamang Baru which have extensive hills from the northwest to the southeast, so the microwave link becomes not Line of Sight. To overcome this problem to do adding a passive repeater back to back. it is placed on a link with the highest elevation site. However, because it works on microwave long haul. Optimization becomes ineffective because passive repeaters back to back are inefficient and used only on short paths so need to reconfiguration link with a space diversity. While space diversity is not effective in the mountains area with a hight terrain rougness. Design of microwave link use passive repeater back to back with a hight terrain rougness and microwave long haul, receive signal level of -71.74 dB, fading margin of 24.26 dB and availability of 99.97712%. However, the availability not yet reached by ITU G.827 and F.1703 standards. Then the microwave link reconfiguration with a space diversity to improve availability, results the space standard by 180λ receive a signal level of -71.39 dBm, fading margin of 24.61 dB and availability of 99.9929% according to the target by ITU G.827 and F.1703 standards. Microwave links with very high integrity and outage time of 8.6 seconds perday.